2019
DOI: 10.1039/c9tc00862d
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing geminate recombination losses in small-molecule-based organic solar cells

Abstract: Small-molecule-based organic solar cells (OSCs) are a recurrent alternative to polymer-based OSCs. Due to the higher purity and definition of small molecules compared to polymers, the morphological requirements can be more relaxed. Here, we present a series of novel rhodanine-based small molecule electron donors and blend them with the standard acceptor PC70BM. By performing a target analysis on femtosecond spectroscopy data, we quantify the rates of geminate charge recombination. We are able to reproduce thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…, E LUMO = − e ( E 1/2 + 4.4 eV) and E LUMO = E HOMO + E g,opt , where E g,opt is the absorption threshold which is obtained from the absorption maxima of the UV spectrum (in acetonitrile). 38 To have a fair comparison, CV measurements for all synthesized PDI s were performed in acetonitrile solution at 100 mV s −1 (Fig. 8b) in a similar way.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, E LUMO = − e ( E 1/2 + 4.4 eV) and E LUMO = E HOMO + E g,opt , where E g,opt is the absorption threshold which is obtained from the absorption maxima of the UV spectrum (in acetonitrile). 38 To have a fair comparison, CV measurements for all synthesized PDI s were performed in acetonitrile solution at 100 mV s −1 (Fig. 8b) in a similar way.…”
Section: Resultsmentioning
confidence: 99%
“…The frontier molecular orbitals (absolute HOMO and LUMO energy levels) were estimated based on the absolute energy of Fc/Fc + by using the equations from the empirical formulas, viz., E LUMO = Àe(E 1/2 + 4.4 eV) and E LUMO = E HOMO + E g,opt , where E g,opt is the absorption threshold which is obtained from the absorption maxima of the UV spectrum (in acetonitrile). 38 To have a fair comparison, CV measurements for all synthesized PDIs were performed in acetonitrile solution at 100 mV s À1 (Fig. 8b) in a similar way.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…17 Sandoval-Torrientes et al studied rhodamine dye-based small molecules (donor) blended with PC 70 BM (acceptor), focusing on the minimization of geminate recombination losses. 18 Shi et al have reported a prototypical all-small-molecule blend, having localized neutral and charged excitons, and the high internal quantum yields attributing to highly activated charge recombination in the Marcus inverted region. 19 The big challenge for SM OPVs is to have chromophores that are panchromatic absorbers, highly stable and easy to construct.…”
Section: Introductionmentioning
confidence: 99%
“…Small molecule semiconductors have attracted great interest due to their well-defined chemical structures, easy purifications, electronic and optical properties, and overcoming the batch-tobatch variation problems. [1][2][3] Lots of small molecules have already been studied in the field of organic photovoltaics, [4][5][6][7][8][9] photocatalytic water splitting, [10] transistors, [11][12][13] organic light emitting diodes, [14] fluorescent probes, [15,16] biosensors, [17] solar cells, [18][19][20][21][22][23][24][25][26][27][28][29] laser writing [30] and nanomedicine [31] as alternatives to conventional semiconductors. Organic small molecules have also been used as electron and hole transporting materials (ETMs and HTMs) in perovskite solar cells, [32][33][34] which has high energy conversion efficiencies (19 % higher), [34,35] and in electrochemical biosensors.…”
Section: Introductionmentioning
confidence: 99%